Peak oxygen uptake in male swimmer and schoolchildren - Emilson Colantonio; Ronaldo Vilela Barros; Maria Augusta Peduti Dal´ Molin Kiss (Universidade Federal de Santa Catarina, 2008)
The objectives of this study were: a) to analyze the behavior of VO2MAX (absolute and relative) of males of differentage groups sex; b) to compare VO2MAX (absolute and relative), of swimmers (SWM) and schoolchildren (SCH) in the sameage groups. Seventy-one boys aged 7-17 years were evaluated (35 SWM and 36 SCH) and distributed into the age groups7-10, 11-14 and 15-17 years. Anthropometric measurements were taken (height, body mass and sum of skin folds) and themetabolic (VO2MAX) tests were carried out using VO2000® gas analysis and an Inbrasport ATL® treadmill, using a modifiedversion of the Bruce protocol. Statistical analysis: ANOVA for repeated measures, followed by Tukey's post hoc test (p<0.05).Absolute VO2MAX: there were statistically significant differences between all age groups and between SWM (0.99 + 0.20and 1.27 + 0.21 L.min-1) and SCH (0.98 + 0.36 and 0.80 + 0.12 L.min-1). Relative VO2MAX: there were statistically significantdifferences between SWM1 and SWM2 (10.88 + 0.09 and 0.75 + 0.47 ml.kg-1.min-1) and between SCH1 and SCH3 (6.96+ 1.23 and 0.98 + 2.29 ml.kg-1.min-1), although SWM and SCH were different. The results indicate that VO2MAX increasedas the subjects got older, which is the result of natural development. However, the effect of swimming training predominated.Although the behavior of the variable was similar for the 11-14 and 15-17 age groups, the figures for SWM and SCH aredifferent at these ages, with the swimmers having higher VO2MAX